Physiological factors in middleweight boxing performance - Guidetti, L.; Musulin, A.; Baldari, C. (The Journal of Sports Medicine and Physical Fitness, 2002)
BACKGROUND: We examined, within the middleweight class, the relationship between ranking in boxing competition performance and some physiological factors. METHODS: Eight elite Italian amateur boxers (first series of AIBA ranking) were assessed in 2 testing sessions, a week apart. In the first testing session all subjects underwent anthropometric measurements from which body fat percentage, upper arm and forearm muscle cross-sectional areas were estimated. In the second testing session all subjects performed grip strength measures and a maximal treadmill test to assess oxygen consumption (VO2), blood lactate and heart rate at maximal effort, at individual anaerobic threshold, and at individual ventilatory threshold. The athletes were ranked following the criteria of world amateur AIBA ranking. In this ranking the first ranked boxer had the highest score gained participating in international tournaments. RESULTS: A Spearman rho correlation analysis revealed that the VO2 at individual anaerobic threshold (46.0+/-4.2 ml x kg-1 x min-1, r=0.91) and the hand-grip strength (58.2+/-6.9 kg, r=0.87) were highly related (p<0.01) to boxing competition ranking. VO2max (57.5+/-4.7 ml x kg-1 x min-1, r=0.81) and wrist girth (17.6+/-0.6 cm, r=0.78) were moderately (p<0.05) related. CONCLUSIONS: These data suggest that there are two basic factors related to boxing performance: physical fitness as indicated by individual anaerobic threshold and maximal oxygen consumption, and upper-body muscular strength as indicated by hand-grip strength.